An Overview of Mixed Polyanionic Cathode Materials for Sodium‐Ion Batteries. Issue 4 (17th September 2018) - Senthilkumar, Baskar; Murugesan, Chinnasamy; Sharma, Lalit; Lochab, Shubham; Barpanda, Prabeer
Abstract: "Building better batteries" remains an ongoing process to cater diverse energy demands starting from small‐scale consumer electronics to large‐scale automobiles and grid storage. While Li‐ion batteries have carried this burden over the last three decades, the ever‐growing and highly diverse applications (based on size, energy‐density, and stationary vs mobile usages) have led to an era of "beyond lithium‐ion batteries." In this postlithium‐battery era, sodium‐ion batteries (NIBs) have emerged as a pragmatic option particularly for large‐scale applications. They attract attention due to the abundance and uniform geographic distribution of sodium‐based minerals, materials/process economy, and well‐known (de)intercalation mechanisms, in particular for stationary applications independent of size/weight restriction. Parallel to the Li‐ion batteries, the cathode (positive electrode) plays a key role in overall performance, leading to the exploration of various layered and 3D framework insertion materials. While layered oxides deliver high capacity, polyanionic hosts offer structural stability, operational safety, and tunable redox potentials. It can be further exploited in "mixed polyanion" cathode materials combining more than one kind of polyanion units. This article focuses on mixed polyanionic cathode materials for NIBs. It renders a sneak‐peek on suites of mixed polyanionic insertion materials discussing their structure, overall electrochemical performance, and future perspectives. Abstract : The polyanionic family of battery electrodes offers structural stability, operational safety, and tunable redox potentials. Going a step further, "mixed polyanionic cathode materials" form a niche sector combining more than one kind of polyanion units. This article renders a sneak‐peek on suites of mixed polyanionic cathode materials for sodium‐ion batteries discussing their structure, overall electrochemical performance, and future perspectives.